2021
DOI: 10.1139/bcb-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin and oral pathologies: a therapeutic treatment

Abstract: The oral cavity is a non-uniform, extraordinary environment characterized by mucosal, epithelial, abiotic surfaces and secretions as saliva. Aerobic and anaerobic commensal and pathogenic microorganisms colonize the tongue, teeth, jowl, gingiva and periodontium. Commensals exert an important role in host defenses, while pathogenic microorganisms can nullify this protective function causing oral and systemic diseases. Every day, 750-1,000 ml of saliva, containing several host defense constituents including lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…Finally, the CLUSTER S/SEV OSCC_LNM was specifically associated to GO groups related to activities against pathogen agents, such as "metal sequestration by antimicrobial proteins" (associated to LCN2, LTF, S100A9-see Table 6 for the FC in S/SEV OSCC_LNM); "growth of symbiont in host" (associated to ELANE, MPO, PGLYRP1-see Table 6 for the FC in S/SEV OSCC_LNM); and "antimicrobial peptides" (associated to ELANE, GAPDH, LCN2, LTF, MPO, PGLYRP1, PI3, PRTN3, RNASE3, S100A12, S100A9-see Table 6 for the FC in S/SEV OSCC_LNM). Proteins of these groups, such as lactoferrin (LFT,), lipocalin-2 (LCN2), S100A9 (forming with S100A8 the heterodimeric complex calprotectin), neutrophil elastase (ELANE), peptidoglycan recognition protein 1 (PGLYRP1), and myeloperoxidase (MPO), are widely described for their antibacterial activity or for their role as inflammatory markers [44][45][46][47][48]. The enrichment of these proteins in the S/SEVs from patients with OSCC_LNM could be indicative of dysbiotic signatures occurring during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the CLUSTER S/SEV OSCC_LNM was specifically associated to GO groups related to activities against pathogen agents, such as "metal sequestration by antimicrobial proteins" (associated to LCN2, LTF, S100A9-see Table 6 for the FC in S/SEV OSCC_LNM); "growth of symbiont in host" (associated to ELANE, MPO, PGLYRP1-see Table 6 for the FC in S/SEV OSCC_LNM); and "antimicrobial peptides" (associated to ELANE, GAPDH, LCN2, LTF, MPO, PGLYRP1, PI3, PRTN3, RNASE3, S100A12, S100A9-see Table 6 for the FC in S/SEV OSCC_LNM). Proteins of these groups, such as lactoferrin (LFT,), lipocalin-2 (LCN2), S100A9 (forming with S100A8 the heterodimeric complex calprotectin), neutrophil elastase (ELANE), peptidoglycan recognition protein 1 (PGLYRP1), and myeloperoxidase (MPO), are widely described for their antibacterial activity or for their role as inflammatory markers [44][45][46][47][48]. The enrichment of these proteins in the S/SEVs from patients with OSCC_LNM could be indicative of dysbiotic signatures occurring during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of Lf to engage with particular receptors on a wide range of immune cells, such as neutrophils, monocytes, macrophages, and lymphocytes, as well as epithelial cells. It indicates that Lf anti-inflammatory action could be responsible for the observed influence on modifying cytokine secretion by these cells primarily through receptor-mediated signaling mechanisms 105 . In a sheep model of allergic asthma caused by tryptase imbalances, several additional mechanisms by which Lf may inhibit the inflammatory reaction have been proposed, including the prevention of iron-catalyzed complimentary radical deterioration at areas of inflammation and the elimination of later stages airway blockage and hyperresponsiveness 60 .…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…The concentration of salivary hLf in healthy subjects ranges between 3.9 and 14.5 µg/ml ( 99 ) with mean values of 8.96 and 7.11 µg/ml in unstimulated and stimulated saliva, respectively as has been reported by authors ( 100 ). Salivary hLf concentration is also influenced by gender ( 34 ), age ( 101 , 102 ), and the physiological or pathological status of the subject ( 99 , 103 – 105 ). Concerning the pathological status of the subjects, a cross-sectional study showed that salivary hLf levels are decreased in patients suffering from mild cognitive impairment (MCI) and AD compared with age-matched healthy subjects ( 16 ), indicating a putative link between AD, the immune system, and brain infections.…”
Section: Introductionmentioning
confidence: 99%